2022
DOI: 10.1111/cch.12984
|View full text |Cite
|
Sign up to set email alerts
|

Programmes to support paediatric to adult healthcare transitions for youth with complex care needs and their families: A scoping review

Abstract: Background: An increasing number of children have complex care needs (CCN) that impact their health and cause limitations in their lives. More of these youth are transitioning from paediatric to adult healthcare due to complex conditions being increasingly associated with survival into adulthood. Typically, the transition process is plagued by barriers, which can lead to adverse health consequences. There is an increased need for transitional care interventions when moving from paediatric to adult healthcare. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 99 publications
2
12
0
Order By: Relevance
“…The M age of our sample, 25 years, highlights that these logistical barriers are likely particularly difficult for young adult CCS who are members of the workforce and may have families that depend on them 26,27 . This aligns with prior research in CCS identifying that macro-level barriers, like difficulty booking appointments, is a common barrier to follow-up care, 24,28–30 and with research among young adults with childhood chronic illnesses that experienced transportation concerns and scheduling changes as barriers to transitioning to adult care 31,32 . This study extends these general findings by examining the item-level barriers; we found that CCS reported the lack of after hours and weekend clinic availability and difficulty taking time off work as specific barriers to scheduling appointments for follow-up care.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The M age of our sample, 25 years, highlights that these logistical barriers are likely particularly difficult for young adult CCS who are members of the workforce and may have families that depend on them 26,27 . This aligns with prior research in CCS identifying that macro-level barriers, like difficulty booking appointments, is a common barrier to follow-up care, 24,28–30 and with research among young adults with childhood chronic illnesses that experienced transportation concerns and scheduling changes as barriers to transitioning to adult care 31,32 . This study extends these general findings by examining the item-level barriers; we found that CCS reported the lack of after hours and weekend clinic availability and difficulty taking time off work as specific barriers to scheduling appointments for follow-up care.…”
Section: Discussionsupporting
confidence: 78%
“…26,27 This aligns with prior research in CCS identifying that macro-level barriers, like difficulty booking appointments, is a common barrier to follow-up care, 24,[28][29][30] and with research among young adults with childhood chronic illnesses that experienced transportation concerns and scheduling changes as barriers to transitioning to adult care. 31,32 This study extends these general findings by examining the item-level barriers; we found that CCS reported the lack of after hours and weekend clinic availability and difficulty taking time off work as specific barriers to scheduling appointments for follow-up care. Improvements in scheduling and after hours/ weekend accessibility may improve CCS adherence to clinical guidelines.…”
Section: Discussionsupporting
confidence: 64%
“…While long-term survival of children with chronic illness has become possible with developing medical care and attention given to health care transition ( 6 ), their siblings also face the risk of psychosocial and emotional difficulties, leading to developmental difficulties and concerns beyond the typical adolescence and young adulthood ( 7 ). It is crucial to support them in promoting self-reliance from childhood, vital for personality growth, to prevent or reduce these concerns throughout their lives.…”
Section: Introductionmentioning
confidence: 99%
“…Optimizing this process is not an easy task, because it depends on several factors including practice's style of health professionals, structure of pediatric and adult services, and adaptation of patients and caregivers to the transition process. [5][6][7][8] In addition, it is known how difficult it is for adolescents and young adults with chronic diseases to become self-sufficient and be able to deal independently with their illnesses. 9,10 There is no ideal transition model, and many pediatric rheumatology services do not have an established transition program.…”
mentioning
confidence: 99%
“…It is well known that an effective transition is associated with better adherence to treatment and better outcomes of chronic diseases. Optimizing this process is not an easy task, because it depends on several factors including practice's style of health professionals, structure of pediatric and adult services, and adaptation of patients and caregivers to the transition process 5–8 . In addition, it is known how difficult it is for adolescents and young adults with chronic diseases to become self-sufficient and be able to deal independently with their illnesses 9,10 …”
mentioning
confidence: 99%